Identification of a cis-acting element in the class I major histocompatibility complex gene promoter responsive to activation by retroviral sequences. - Choi, S Y (1997)
The infection of cells with Moloney murine leukemia virus (M-MuLV) causes an increase in specific cellular gene products, including the major histocompatibility complex (MHC) class I antigens. This upregulation occurs through a transactivation process mediated by the long terminal repeat (LTR) of M-MuLV, and we show here that the gene activation response to the LTR requires at least one specific cis element within the MHC proximal promoter region. Nested deletions of MHC class I H-2Kb gene promoter sequence were subcloned into a chloramphenicol acetyltransferase (CAT) reporter vector and then transiently introduced into BALB/c-3T3 cells expressing M-MuLV or cotransfected into BALB/c-3T3 cells with a vector containing subgenomic portions of the virus, including the LTR. CAT activity assays demonstrated that a minimal H-2Kb gene promoter (-64 to +12) contained elements sufficient for this transactivation. DNase I footprinting assays located a protein-binding site in the region of -64 to -34 bp from the transcriptional start site, and point mutation analysis confirmed the location of this cis-acting element, designated the let response element (LRE), and defined a binding motif. This LRE is distinct from binding sites for currently known transcription factors in the class I MHC gene promoter and is conserved in the promoters of human and murine MHC class I genes. Mutation of the LRE resulted in dramatic reduction in both DNA-protein binding activity in electrophoretic mobility shift assay and in the ability of the mutated promoter to respond to retroviral transactivation. Addition of the LRE to a heterologous promoter conferred the ability to respond to retroviral transactivation.